2015
DOI: 10.1371/journal.pone.0128982
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Influenza A/PR/8/34 Donor Viruses Imparting High Hemagglutinin Yields to Candidate Vaccine Viruses in Eggs

Abstract: One of the important lessons learned from the 2009 H1N1 pandemic is that a high yield influenza vaccine virus is essential for efficient and timely production of pandemic vaccines in eggs. The current seasonal and pre-pandemic vaccine viruses are generated either by classical reassortment or reverse genetics. Both approaches utilize a high growth virus, generally A/Puerto Rico/8/1934 (PR8), as the donor of all or most of the internal genes, and the wild type virus recommended for inclusion in the vaccine to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
2
24
1
Order By: Relevance
“…the phenotypic character of avirulence in chickens ( Table 2). 33 Taken together, these studies strongly support the absolute necessity of a basic amino acid cluster or insertion of additional amino acids at the cleavage site to impart high virulence for chickens to reassortant viruses with PR8 genetic background.…”
Section: B I Osafe T Y Record Of C V V S Since 2 0 0mentioning
confidence: 55%
See 1 more Smart Citation
“…the phenotypic character of avirulence in chickens ( Table 2). 33 Taken together, these studies strongly support the absolute necessity of a basic amino acid cluster or insertion of additional amino acids at the cleavage site to impart high virulence for chickens to reassortant viruses with PR8 genetic background.…”
Section: B I Osafe T Y Record Of C V V S Since 2 0 0mentioning
confidence: 55%
“…The numerous CVVs developed to protect against H5 and H7 HPAI virus subtypes, comprising diverse HA and NA genetic lineages (Eurasian and North American) and divergent genetic clades (Table ), were produced by reverse geneticā€engineered reassortment with a human virus adapted for optimal growth in eggs, usually A/Puerto Rico/8/34 (PR8) or its derivatives . Despite extensive genetic diversity in the HA/NA and some variation among backbone virus genes, all CVVs and veterinary vaccine viruses shared the phenotypic character of avirulence in chickens (Table ) . Taken together, these studies strongly support the absolute necessity of a basic amino acid cluster or insertion of additional amino acids at the cleavage site to impart high virulence for chickens to reassortant viruses with PR8 genetic background.…”
Section: Biosafety Record Of Cvvs Since 2004mentioning
confidence: 99%
“…Parallel work that can occur further downstream of the safety testing of the CVV involves analysis of HA yield and further improvements in growth characteristics necessary for large-scale expansion and stockpiling. Specifically, alternate PR/8 internal gene segments with different characteristics can be combined with the HA and NA from the CVV in order to optimize yield through different gene segment interactions (Johnson et al, 2015). In addition, further passaging in eggs is another approach to elicit egg-adapted changes that can improve yield while maintaining antigenicity similarity to parental virus (Ridenour et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the majority of NP-specific T-cell epitopes of currently circulating viruses could be incorporated without a loss of seed virus yield. Moreover, a recent study suggested that the surface proteins, HA and NA, rather than internal and non-structural proteins, had the strongest impact on reassortant growth properties [15]. We therefore strongly recommend that the wild-type NP gene be included in the genome of reassortant viruses generated for IIV.…”
Section: Reassortant Viruses For Influenza Vaccines: Is It Time To Rementioning
confidence: 99%